2021
DOI: 10.1002/2211-5463.13335
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast genomes of two Pueraria DC. species: sequencing, comparative analysis and molecular marker development

Abstract: Puerariae lobatae radix (Ge-Gen in Chinese) and Puerariae thomsonii radix (Fen-Ge) are widely used as medicine and health products, particularly in Chinese medicine. Puerarin and daidzein are the primary bioactive compounds in Puerariae radix. These isoflavones have been used to treat cardiovascular and cerebrovascular diseases, hypertension, diabetes, and osteoporosis. The content of puerarin in Ge-Gen is about six times higher than that in Fen-Ge, so its use has a higher pharmacological effect. It is therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
(51 reference statements)
1
2
0
Order By: Relevance
“…The arrangement and recombination of the cp genome may be significantly influenced by the regions and the numbers of the repeat sequences [61]. The long repeat sequence analysis revealed that palindromic and forward repeats were the most common repeats in E. cymosa and E. obtusifolia (Figure 5), which is consistent with other angiosperm cp genome analyses [62][63][64][65][66]. The SSRs analysis showed that the cp genomes of E. cymosa and E. obtusifolia comprised 141 SSRs and 139 SSRs, respectively (Table 2).…”
Section: Discussionsupporting
confidence: 84%
“…The arrangement and recombination of the cp genome may be significantly influenced by the regions and the numbers of the repeat sequences [61]. The long repeat sequence analysis revealed that palindromic and forward repeats were the most common repeats in E. cymosa and E. obtusifolia (Figure 5), which is consistent with other angiosperm cp genome analyses [62][63][64][65][66]. The SSRs analysis showed that the cp genomes of E. cymosa and E. obtusifolia comprised 141 SSRs and 139 SSRs, respectively (Table 2).…”
Section: Discussionsupporting
confidence: 84%
“…The long repeat sequence analysis of E. strigosa , H. arbainense , and H. longiflorum recognized the forward and palindromic repeats were the most common repeats (Fig. 5 and Tables S9 , S10 , and S11 ), as found in the most angiosperm plastomes [ 60 64 ]. The number and regions of repeat sequences might influence the recombination and arrangement processes within the plastome [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number and regions of repeat sequences might be the reason for the recombination and arrangement events in the chloroplast genome [71]. The palindromic and forward repeats are the dominant types of repeats in the angiosperm plastomes [72][73][74]. The SSRs analysis revealed that both genomes contained 155 microsatellites (Table 2).…”
Section: Discussionmentioning
confidence: 99%